Applications of Nanotechnology in Diabetes - Anusha, Dasari; Pradeep, Karumanchi (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
Nanotechnology offers sensing technologies that provide more accurate and timely medical information for diagnosing disease, and miniature devices that can administer treatment automatically if required. Some tests such as diabetes blood sugar levels require patients to administer the test themselves to avoid the risk of their blood glucose falling to dangerous levels. Certain users such as children and the elderly may not be able to perform the test properly, timely or without considerable pain. Nanotechnology can now offers new implantable and/or wearable sensing technologies that provide continuous and extremely accurate medical information.The purpose of this review is to throw more light on the recent advances and impact of nanotechnology on biomedical sciences to cure diabetes.